Field observation on the use of PRID®Delta to induce estrus and ovulation in anestrous mares - mebarki, mounir; Kaidi, R; Basbaci, M (Journal of the Hellenic Veterinary Medical Society, 2022)
To advance the time of the first estrus with ovulation, we administered intravaginally a progesterone-releasing devices PRID® Delta to 42 acyclic Arab-Barb mares for 11 days at different seasons: winter (n = 10), spring (n = 14), summer (n = 9) and autumn (n = 9). Twenty-seven of 39 mares that kept their coils responded to the PRID® Delta treatment with estrus and ovulation during the 42-day observation period, in winter (4/10, 40%) mares, in spring (9/13, 69%), in summer (7/7, 100%) and autumn (7/9, 78%) mares (P <0,05). At Day 2 of PRID® Delta treatment, mean initial of progesterone concentrations was significantly increased in all mares in winter (7.20 ± 0.49 ng mL-1), spring (7.30 ± 0.64 ng mL-1), summer (7.5 ± 0.58 ng mL-1 ) and autumn ( 7.60 ± 0.71 ng mL-1) (P <0,05). Total concentration of progesterone (area under curve (AUC)) during the treatment period revealed highest values in spring (67.95 ± 2.40 ng mL-1h-1) followed by autumn (65.20 ± 1.37 ng mL-1 h-1), winter (54.19 ± 7.00 ng mL-1 h-1) and summer 52.23 ± 3.32 ng mL-1 h-1; P < 0.05). In conclusion, administration of the intravaginal device releasing progesterone PRID® Delta was able to induce estrus and ovulation in mares at different times of the year. However, the efficacy of the treatment was not satisfactory in terms of efficacy compared to the season (low response rate in winter) and synchrony of intervals from removal of PRID® Delta to ovulation.